Colorectal cancer in Jordan: prevention and care. (December 2015) - Ahmad, Muayyad M.; Dardas, Latefa; Dardas, Lubna; Ahmad, Huthaifa
The aim of this study was to describe the knowledge, attitudes, and practices toward colorectal cancer prevention and care in Jordan. A survey was designed to produce reliable estimates for the population's knowledge, attitudes, and practices in all 12 governorates of Jordan by using stratified random sampling. A representative sample of the adult population in Jordan completed a comprehensive tool which explored participants' knowledge about the risk factors associated with colorectal cancer, cancer prevention through lifestyle changes, and early cancer diagnosis and screening. According to the participants ( n = 3196), colorectal cancer had the second highest percentage of screening recommendation (12.6%) after breast cancer (57.3%). Only 340 individuals (11%) reported ever screening for cancer. About 20% of the participants had heard of one of the screening tests for colorectal cancer. In fact, only 290 (9.1%) participants had performed the colorectal cancer screening tests. This study provides data that will help colorectal cancer prevention and treatment programs and may enhance the efficiency of colorectal cancer-controlling programs. The findings confirm the necessity of starting colorectal screening intervention that targets the most vulnerable individuals.